Surface degradation of composite resins under staining and brushing challenges - Tânia Mara da Silva; Débora Cristina Barbosa Dantas; Tainá Teixeira Franco; Lucas Teixeira Franco; Maria Filomena Rocha Lima Huhtala (Elsevier, 2019)
Background/purpose: The primeval evaluation of the properties of composite resins with different compositions that impact clinical behavior is very important in guiding use in clinical settings. The aim of this study was to evaluate color stability (ΔE) and Knoop microhardness (KHN) of composite resins containing different compositions. Materials and methods: Forty-five disks were made composite resins: Filtek Z350 XT/3MESPE and Beautifill II/SHOFU and divided into 3 subgroups: Control - immersed in artificial saliva; OB - brushing with Oral B 3D White; CT - brushing with Colgate Total 12. The OB and CT groups had the disks brushed daily with 120 cycles after immersion in coffee solution (10 min) for a period of 30 days. ΔE and KHN was obtained at baseline and after the treatments. Data were analyzed ANOVA and Tukey tests (p < 0.05). Results: ANOVA revealed significant differences for ΔE and KHN. ΔE: the highest mean was observed in Beautifil II composite resin group, which differed significantly from Z350 group. For the Beautifil II, the treatments were significantly different from each other. For the Z350, the control group showed significant differences in relation to OB e CT groups. KHN: the highest mean was observed in Z350 group, which differed significantly from Beautifil II group. For Z350, the control group showed significant differences in relation to OB e CT groups. For Beautifil II, the treatments did not differ significantly among themselves. Conclusion: The composite resin containing fluoride in the composition showed higher color alteration (ΔE) and lower Knoop microhardness (KHN), thus demonstrating that composition is an important factor in the clinical performance of esthetic restorative materials. Keywords: Color, Composite resins, Hardness, Toothpastes